2007
DOI: 10.1158/0008-5472.can-07-2667
|View full text |Cite|
|
Sign up to set email alerts
|

Therapeutic Efficacy of a Novel Focal Adhesion Kinase Inhibitor TAE226 in Ovarian Carcinoma

Abstract: Focal adhesion kinase (FAK) overexpression is frequently found in ovarian and other cancers and is predictive of poor clinical outcome. In the current study, we characterized the biological and therapeutic effects of a novel FAK inhibitor, TAE226. Taxane-sensitive (SKOV3ip1 and HeyA8) and taxaneresistant (HeyA8-MDR) cell lines were used for in vitro and in vivo therapy experiments using TAE226 alone and in combination with docetaxel. Assessment of cytotoxicity, cell proliferation [proliferating cell nuclear an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
198
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 196 publications
(204 citation statements)
references
References 45 publications
6
198
0
Order By: Relevance
“…This recently developed low molecular weight inhibitor is well characterised as preventing FAK activation via blockade of tyrosine phosphorylation (Halder et al, 2007;Shi et al, 2007). However the application of 500nM TAE226 did not inhibit MG63 maturation in response to LPA/ colchicine and D 3 (data not shown).…”
Section: Discussionmentioning
confidence: 92%
“…This recently developed low molecular weight inhibitor is well characterised as preventing FAK activation via blockade of tyrosine phosphorylation (Halder et al, 2007;Shi et al, 2007). However the application of 500nM TAE226 did not inhibit MG63 maturation in response to LPA/ colchicine and D 3 (data not shown).…”
Section: Discussionmentioning
confidence: 92%
“…Early studies in ovarian cancer cell lines and xenografts demonstrated that knockdown of FAK expression enhanced docetaxel efficacy in docetaxelsensitive and docetaxel-resistant models in vitro and in vivo (31,32). Subsequently, TAE226, a TKI that targets FAK and IGF-1R, was demonstrated to enhance docetaxel cytotoxicity (33); however, at this point, development stalled due to the drug failing clinical trials. Other firstgeneration FAK TKIs had problems with compensatory upregulation of the FAK homolog, Pyk2, which affected clinical efficacy (34).…”
Section: Discussionmentioning
confidence: 99%
“…This approach is supported by studies that have reported sensitisation to 5-fluorouracil (5-FU) and a partial reversion of 5-FU resistance when FAK is suppressed (Chen et al 2009). Moreover, TAE226, a pharmacological inhibitor of FAK phosphorylation (Y397 and Y861), augments docetaxel sensitivity in taxane-resistant ovarian cancer cells (Halder et al 2007). In such contexts, FAK may represent a convergence point for multiple signalling pathways that may contribute to resistance, highlighting its potential importance as a therapeutic target.…”
Section: Discussionmentioning
confidence: 99%